Evaluation of the Appropriate Perioperative Antibiotic Prophylaxis in Italy - Napolitano, Francesco; Izzo, Maria Teresa; Di Giuseppe, Gabriella; Angelillo, Italo F.; and the Collaborative Working Group (PLOS ONE, 2013)
Background The appropriate use of antibiotics prophylaxis in the prevention and reduction in the incidence of surgical site infection is widespread. This study evaluates the appropriateness of the prescription of antibiotics prophylaxis prior to surgery amongst hospitalized patients in the geographic area of Avellino, Caserta, and Naples (Italy) and the factors associated with a poor adherence. Methods A sample of 382 patients admitted to 23 surgical wards and undergoing surgery in five hospitals were randomly selected. Results Perioperative antibiotic prophylaxis was appropriate in 18.1% of cases. The multivariate logistic regression analysis showed that patients with hypoalbuminemia, with a clinical infection, with a wound clean were more likely to receive an appropriate antibiotic prophylaxis. Compared with patients with an American Society of Anesthesiologists (ASA) score ≥4, those with a score of 2 were correlated with a 64% reduction in the odds of having an appropriate prophylaxis. The appropriateness of the timing of prophylactic antibiotic administration was observed in 53.4% of the procedures. Multivariate logistic regression model showed that such appropriateness was more frequent in older patients, in those admitted in general surgery wards, in those not having been underwent an endoscopic surgery, in those with a higher length of surgery, and in patients with ASA score 1 when a score ≥4 was chosen as the reference category. The most common antibiotics used inappropriately were ceftazidime, sultamicillin, levofloxacin, and teicoplanin. Conclusions Educational interventions are needed to improve perioperative appropriate antibiotic prophylaxis.